Subjective consistency increases trust - Andrzej Nowak; Mikolaj Biesaga; Karolina Ziembowicz; Tomasz Baran; Piotr Winkielman (Scientific Reports, 2023)
Abstract Trust is foundational for social relations. Current psychological models focus on specific evaluative and descriptive content underlying initial impressions of trustworthiness. Two experiments investigated whether trust also depends on subjective consistency—a sense of fit between elements. Experiment 1 examined how consistency of simple verbal characterizations influences trust judgments. Experiment 2 examined how incidental visual consistency impacts trust judgments and economic decisions reflecting trust. Both experiments show that subjective consistency positively and uniquely predicts trust judgments and economic behavior. Critically, subjective consistency is a unique predictor of trust that is irreducible to the content of individual elements, either on the dimension of trust or the dimension of valence. These results show that trust impressions are not a simple sum of the contributing parts, but reflect a “gestalt”. The results fit current frameworks emphasizing the role of predictive coding and coherence in social cognition.